Inspection process and procedure in architecture work on the Residence Condominium, Bukit OUG, Kuala Lumpur / Marni Ainin Syahirah Muksain - Muksain, Marni Ainin Syahirah (Universiti Teknologi Mara, Perak, 2014)
PutrajayaPerdanaBerhad (PPB) is an accomplished and large scale of company that involved in the construction, property development and concession player in Malaysia. Our success in delivering several prominent and large scale projects on a turnkey, design and build basis, as well as our pioneering efforts in energy efficiency in construction, have done much to enhance our reputation as one of Malaysia’s most innovative and reliable construction companies.